2018
DOI: 10.47125/jesam/2018_2/05
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Total Quality Management and Environmental Management System on Sustainable Performance of Selected Industries in Pakistan

Abstract: The concept of sustainability has gained due attention and recognition over the years, which has fundamentally broadened the scale of organizational mission in three dimensions of sustainability. To attain sustainable performance, organizations have been using various strategies, among which is Total Quality Management (TQM) that is recognized as the most famous. The ISO 14001 Environmental Management System (EMS) standard can also be beneficial to address sustainabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Both philosophies take a proactive stance in which managers' focus on long-term goals, maintaining performance achievements, zero-defect approach, waste reduction, life cycle assessment, employee participation, and training (Seth et al, 2018). Hence, inadequate quality practices damage the company's environmental performance capabilities and can, in return, harm organizational reputation and financial performance (Tasleem et al, 2018;Sharma et al, 2019). Moreover, Habib et al (2019) found that poor quality practices indicate a weak application of GM, as it contributes to wasting human efforts and natural resources.…”
Section: Tqm and Gmmentioning
confidence: 99%
“…Both philosophies take a proactive stance in which managers' focus on long-term goals, maintaining performance achievements, zero-defect approach, waste reduction, life cycle assessment, employee participation, and training (Seth et al, 2018). Hence, inadequate quality practices damage the company's environmental performance capabilities and can, in return, harm organizational reputation and financial performance (Tasleem et al, 2018;Sharma et al, 2019). Moreover, Habib et al (2019) found that poor quality practices indicate a weak application of GM, as it contributes to wasting human efforts and natural resources.…”
Section: Tqm and Gmmentioning
confidence: 99%
“…For example, scholars (Li et al, 2018;Zeng et al, 2017) reported a negative association between TQM and GI performance of Chinese firms. Another line of the research (Abbas, 2020;Shahzad et al, 2020;Tasleem et al, 2018) reported a positive relation between TQM and CSD. Some scholars noted that TQM impedes GI, whereas others opined that it promotes GI in firms (Li et al, 2018).…”
Section: Introductionmentioning
confidence: 94%
“…Thus, firms allocate a portion of their resources to environmental and social development programs (Shahzad et al , 2020). CS applies to companies (Tasleem et al , 2018) and has a more appropriate and applicable definition of sustainability in operations, management and business (Franco et al , 2020). CS is an enterprise’s ability to cause minimal influence on the society and environment by using and reducing their natural resources waste to zero, especially the nonrenewable resources (Rehmani et al , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Over time, the idea of sustainability has received the attention and validation it deserves which has fundamentally expanded the scope of organizational mission in three dimensions of sustainability (Zink, 2007). Organizations have been utilizing a variety of ways to achieve sustainable success (Tasleem & Nawar, 2018). In the current environment, sustainability is becoming a top concern for every firm (Sancha et al 2016).…”
Section: Sustainabilitymentioning
confidence: 99%